INFLUENCE OF PHYSICAL EXERCISE DURING MUSCULOSKELETAL GROWTH AND DEVELOPMENT - Mihai Constantinescu; Luţac Sinziana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This article presents a study conducted by questioning of students from three different schools in the city Suceava. This aims to determine the students participate in sports and outside of curriculum hours school. Exercise practiced physical constant may be a factor determining the growth and harmonious development as well as maintaining optimal health status.